Editorial Address on the Coming of Age of the Journal of Elementary Education - Duh, Matjaž (Revija za elementarno izobraževanje, 2025)
Dear readers, esteemed authors, reviewers, and friends of our journal, today we stand before an important milestone – with the last issue of this year (Volume 18, Issue 4), the Journal of Elementary Education has officially come of age. This is not merely a number, but a symbol of the maturity, perseverance, and dedication that have guided us through all the years of our existence. When we set out on this path in 2008 with enthusiasm and courage, the decision to publish four issues per year seemed bold to many. Yet that very decision became the foundation upon which we have built our story. From the first double issues, humble beginnings, and limited resources, to the present day, when the journal stands as a recognized scientific forum, we have proven that perseverance and quality always pay off. Each year brought new challenges and new victories. In 2015, we gained valuable partners – the University of Primorska and Charles University in Prague. In 2019, we reached a turning point: inclusion in the Scopus database, which was both a recognition of our work and a promise for the future. Since 2020, the journal has been published in five issues per year, including special thematic issues that open new research horizons. Today, we can proudly say that more than 760 authors have published in our journal, contributing over 550 scientific papers, reviewed by nearly 800 experts. We receive more than ten submissions weekly, yet because of our high publication standards, we reject an average of 85%. It is precisely this unwavering commitment to quality that has led to our inclusion in the third quartile (Q3) of the global quality ranking as of 2024. The coming of age of our journal is more than a chronological milestone – it is proof that the Journal of Elementary Education has established itself as a reliable companion to researchers, as a space for dialogue, and as an echo of scientific discourse that enriches the field of primary education. Our journal covers a wide range of topics related to primary-level education. On this occasion, we call on colleagues, professors, and researchers to explore our archive when preparing their scientific contributions. We are confident that they will find content that sheds light on new perspectives and can be incorporated into their research. Citing articles from the JEE will contribute to the journal’s international recognition and elevate it further on the quality scale. On this occasion, we extend our sincere gratitude to all who have co-created our journey: the authors, reviewers, partner institutions, and loyal readers. Without your support, our story would be incomplete. May this coming of age mark the beginning of a new era in which we continue to strengthen quality, broaden horizons, and reinforce the importance of scientific inquiry. May the Journal of Elementary Education continue to be a beacon of knowledge, illuminating the path for future generations of researchers and educators. For the Editorial Board of the Journal of Elementary Education Editor-in-Chief Faculty of Education, University of Maribor